Calibration of Accelerometers by Shock Excitation and Laser Interferometry - Alfred Link; Hans-Jüurgen von Martens (Shock and Vibration)
A signal processing method for determining the dynamic behavior of accelerometers by shock excitation and laser interferometry is presented. The method allows the shock sensitivity and the magnitude and phase lag of the complex sensitivity of accelerometers to be accurately measured. After digitizing the phase-modulated signals at the output of a homodyne or heterodyne interferometer, the time-dependent displacement is reconstructed on the basis of the principle of coherent demodulation. Data processing developed for determining peak value and spectrum of the acceleration efficiently suppresses disturbing quantities. Computer simulations and experiments proved that the shock parameters can be measured with expanded uncertainties of less than 0.2%. method has been adopted by the ISO/TC 108/SC 3 as a primary shock calibration method to be specified in a new international standard ISO 16063-13 “Primary shock calibration using laser interferometry”.